Suppressive effects of a transient receptor potential melastatin 8 (TRPM8) agonist on hyperthermia-induced febrile seizures in infant mice - Moriyama, Hiroshi; Nomura, Sadahiro; Imoto, Hirochika; Oka, Fumiaki; Maruta, Yuichi; Mori, Naomasa; Fujii, Natsumi; Suzuki, Michiyasu; Ishihara, Hideyuki (Frontiers in Pharmacology, 2023)
Background: Febrile seizures (FSs) are the most frequent type of seizures in infancy and childhood. Epileptiform discharges (EDs) on electroencephalogram at the time of first FS recurrence can increase the risk of epilepsy development. Therefore, inhibition of EDs is important. Recently, WS-3, a transient receptor potential melastatin 8 (TRPM8) agonist, reportedly suppressed penicillin G-induced cortical-focal EDs. However, the effects of TRPM8 agonists on FSs remain unknown. In this study, we aimed to clarify the effects of the TRPM8 agonist, and the absence of TRPM8 channels, on hyperthermia-induced FS by analyzing the fast ripple band. Methods: Hyperthermia (43°C for 30 min) induced by a heating pad caused FSs in postnatal day 7 wild-type (WT) and TRPM8 knockout (TRPM8KO) mice. FSs were defined as EDs occurring during behavioral seizures involving the hindlimb clonus and loss of the righting reflex. Mice were injected with dimethyl sulfoxide or WS-3 20 min before the onset of hyperthermia, and electroencephalogram, movies, measuring rectal, brain and heating pad temperatures were recorded. Results: In WT mice, WS-3 reduced the fast ripple amplitude in the first FS without changing rectal and brain temperature thresholds. In contrast, the anti-FS effect induced by the TRPM8 agonist was not observed in TRPM8KO mice and, compared with WT mice, TRPM8 deficiency lowered the rectal and brain temperature thresholds for FSs, exacerbated the fast ripple amplitude, and prolonged the duration of the initial FS induced by hyperthermia. Conclusion: Our findings suggest that TRPM8 agonists can be used to treat hyperthermia-induced FSs.